STRATEGI ORANG TUA DALAM MEMBENTUK AKHLAK ANAK USIA SMP-SMA - Wahid Nur Afif; Nuraini; Rohmadi; Karomatul Hidayah (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2025)
Family education is the first stage as an effort to establish children’s morals because family is the first environment for children. From the family, children will get a guidance and coaching especially for religion, so what is gotten from family will be a principle for children in their future life. That principle is expected to establish children’s attitude and mental which accordance with the Islamic law. Children’s association in society becomes a fidgetiness for parents who have teenage children. In this stage, adolescence is a transition period from children to adult which sometimes children rather to follow what they see and what they hear. This research was conducted to know the parent’s strategy in morals establishment of High School level children in Gombang village and to know supporting and inhibiting factors of implemented strategy by parents in establishing children’s morals. The significance of this research are as enriching parents’ insight in knowledge development theoretically and as correction for parents to implement the right strategy in establishing children’s morals. The approach for this research was qualitative approach and the design was descriptive. The data source were primary data and secondary data; parents who have High School level children, village apparatus and High School level children. For the data collection technique, researcher used interview, observation, and documentation. And the data analysis researcher used three steps analysis; data reduction, data display, and conclusion/verification. The result of this research is the strategy which was implemented by parents includes advice giving, controlling all of children’s activity indoor and outdoor, getting used to discipline in praying especially congregational prayer at the mosque, sent the children to the Islamic boarding school, involving children in useful activities and getting used for children to speak politely. The supporting factors are Islamic environment, guiding children to follow useful activities and creating a harmonious family. And the inhibiting factors are children’s association out of family environment, when children are hard to get some guidance, and when children are too busy with their smart phone.